Dugaan Malpraktek Medik & Draf Rpp Perjanjian Terapetik antara Dokter dan Pasien - Guwandi, J (Balai Penerbit FKUI, 2009)
Dugaan Malpraktek Medik & Draf Rpp Perjanjian Terapetik antara Dokter dan Pasien